Investigation of Distinctive Morpho-Physio and Biochemical Alterations in Desi Chickpea at Seedling Stage Under Irrigation, Heat, and Combined Stress - Jameel, Saima; Hameed, Amjad; Shah, Tariq Mahmud (Frontiers in Plant Science, 2021)
Global climatic instabilities have become the main reason for drastic yield losses in chickpea, this shift in climate could be a threat in the future for food security in developing countries. Present study was aimed (i) to investigate the tolerance response of 9 desi chickpea genotypes against heat stress (H), irrigation (I), and a combination of both (I+H) through morphophysiological and biochemical indices at early growth stage (ii) assessment of yield performance across multiple locations of the country. Results revealed that under irrigation treatment all genotypes perform well but the genotypes, D-09027 and D-09013 showed best performance because they retained root length, seedling fresh weight, root fresh weight, root dry weight, esterase activity, MDA content, total chlorophyll and total carotenoids; while shoot length and total phenolic contents (TPC) increased in both; SOD and POD increased in D-09027 and retained in D-09013, catalase activity increased in D-09013 and retained in D-09027; protease activity, total water potential and osmotic potential decreased in both, showed high yield potential with 27% and 30 % increase in yield over Bhakhar-2011 (check) respectively. In case of heat stress, maximum tolerance was found in genotypes CH104/ 06 and D-09013 ,with no change in shoot length, root length, seedling dry weight, shoot fresh weight, shoot dry weight, root dry weight, relative water content, turgor water potential, catalase activity, esterase activity; increased root fresh weight, peroxidase activity (POD), ascorbate peroxidase activity (APX), lycopene, with low accumulation of protease and Malondialdehyde content (MDA), both depicted high yield potential with 30% and 43% increase over check across multiple locations of country. Under the combined treatment mostly genotypes showed good performance, while CH104/06 selected as best performer genotype because significant increased root fresh weight, lycopene content, chlorophyll b, total carotenoids, total chlorophyll; retained shoot length, root length, seedling fresh and dry weight, total water potential, osmotic potential, relative water content, peroxidase activity, catalase, esterase, ascorbate peroxidase activity and total soluble proteins and showed highest yield potential with 43% increase over check. Identified best performing and tolerant genotypes can further be employed for breeding climate-smart chickpea genotypes